Espiritualidade de pessoas vivendo com HIV/AIDS em cuidados paliativos: estudo à luz da teoria de Jean Watson - Vasconcelos, Monica Ferreira de (2020)
Introduction – Spiritual needs motivate people to seek meaning for their lives and help them transcend their troubles and suffering. Spirituality is of paramount importance in nursing assistance to people living with HIV/AIDS under palliative care. This dissertation was composed of three studies which were presented as articles. A review article which aimed to investigate the scientific production with regard to the use of tools for spirituality assessment, within the worldwide scenario context. The work admitted that the majority of the rating scales utilized are easy to be applied and are validated for the Portuguese language, and that besides assessing spirituality, they also measure life quality. The original articles aimed to: evaluate the spirituality of people living with HIV/AIDS, grounded in the Spiritual Health Assessment Scale (SHAS); analyze the comprehension of people living with HIV/AIDS under palliative care with regard to spirituality,in light of Jean Watson’s theory. Methodology – This is a descriptive quantitative-qualitative study, carried out in three hospitals in the city of João Pessoa. Data collection took place between December 2018 and April 2019. For data collection, a tool including questions regarding the participants’ characterization was utilized, Pinto and Pais-Ribeiro’s Spirituality Scale, applied to a sample composed of 152 people, and a semi-structured interview script applied to a sample of 18 people. It was only started after the approval of the Research and Ethic Committee, under technical opinion number 3.056.996. Results - the following studies have emerged from the data collection : (1) Spirituality of patients under palliative care: a study with people living with HIV/AIDS. (2) Spirituality: a study with people living with HIV/AIDS under palliative care in light of Watson’s theory. The first study has shown that statistical differences have occurred in the domain of “Faith”, especially catholic and evangelical practices, among other religions, in the way people living with HIV/AIDS experience their spirituality while coping with their health condition. In the second manuscript, the participants’ discourse analysis has shown that the majority of people living with HIV/AIDS take recourse to spirituality as a way of overcoming and coping with the difficulties which have emerged from their diagnosis. Conclusions – Thus, the relevance of spirituality became evident to the planning of assisting actions for a more comprehensive approach, showing the importance this human dimension represents, especially when it comes to the experiencing of a health-related event. Thus, it is imperative for the professional to know the practices, beliefs and customs of patients in order to assist them better.